Cloud feedback mechanisms and their representation in global climate models. (11th May 2017) - Ceppi, Paulo; Brient, Florent; Zelinka, Mark D.; Hartmann, Dennis L.
Abstract : Cloud feedback—the change in top‐of‐atmosphere radiative flux resulting from the cloud response to warming—constitutes by far the largest source of uncertainty in the climate response to CO2 forcing simulated by global climate models (GCMs). We review the main mechanisms for cloud feedbacks, and discuss their representation in climate models and the sources of intermodel spread. Global‐mean cloud feedback in GCMs results from three main effects: (1) rising free‐tropospheric clouds (a positive longwave effect); (2) decreasing tropical low cloud amount (a positive shortwave [SW] effect); (3) increasing high‐latitude low cloud optical depth (a negative SW effect). These cloud responses simulated by GCMs are qualitatively supported by theory, high‐resolution modeling, and observations. Rising high clouds are consistent with the fixed anvil temperature (FAT) hypothesis, whereby enhanced upper‐tropospheric radiative cooling causes anvil cloud tops to remain at a nearly fixed temperature as the atmosphere warms. Tropical low cloud amount decreases are driven by a delicate balance between the effects of vertical turbulent fluxes, radiative cooling, large‐scale subsidence, and lower‐tropospheric stability on the boundary‐layer moisture budget. High‐latitude low cloud optical depth increases are dominated by phase changes in mixed‐phase clouds. The causes of intermodel spread in cloud feedback are discussed, focusing particularly on the role of unresolved parameterized processes such as cloud microphysics, turbulence, and convection. WIREs Clim Change 2017, 8:e465. doi: 10.1002/wcc.465 This article is categorized under: Climate Models and Modeling > Model Components Abstract : Spatial distribution of cloud feedback (in W m −2 per K surface warming) predicted by a set of global climate models subjected to an abrupt increase in CO2 (Reprinted with permission from Ref 26. Copyright 2016 John Wiley and Sons).